Physical, chemical, and in vitro toxicological characterization of nanoparticles in chemical mechanical planarization suspensions used in the semiconductor industry: towards environmental health and safety assessments1. Issue 3 (5th June 2015) - Speed, David; Westerhoff, Paul; Sierra-Alvarez, Reyes; Draper, Rockford; Pantano, Paul; Aravamudhan, Shyam; Chen, Kai Loon; Hristovski, Kiril; Herckes, Pierre; Bi, Xiangyu; Yang, Yu; Zeng, Chao; et al.
<x xml:space="preserve">Abstract</x> This tutorial review focuses on aqueous slurries of dispersed engineered nanoparticles (ENPs) used in chemical mechanical planarization (CMP) for polishing wafers during manufacturing of semiconductors.